Glutathione Bioresponsive Cyclodextrin Nanosponges. Issue 5 (15th March 2016) - Trotta, Francesco; Caldera, Fabrizio; Dianzani, Chiara; Argenziano, Monica; Barrera, Giuseppina; Cavalli, Roberta
Abstract: Invited for this month's cover is Prof. Francesco Trotta′s group from the University of Torino, Italy. The cover picture shows the chemical structure of a glutathione‐responsive β‐cyclodextrin nanosponge, bearing disulfide bridges and loaded with anticancer doxorubicin (red and white pills). Glutathione thiol groups are able to reduce the nanosponge disulfide moieties. The cleavage of the disulfide bridges allows a targeted release of anticancer drugs into glutathione‐rich chemoresistant tumor cells. Read the full text of the article at 10.1002/cplu.201500531 . Abstract : "… The priceless feeling of finding something unexpected motivates us to explore new research fields, especially in the synthesis of new nanostructured materials and in the design of targeted drug delivery systems. …" Read more about the story behind the cover in the Cover Profile and about the research itself (DOI:10.1002/cplu.201500531 ).